ANALISIS FAKTOR FUNDAMENTAL EKONOMI YANG MEMPENGARUHI RISIKO PINJAMAN LUAR NEGERI INDONESIA - Eka Budiyanti; Lisnawati Lisnawati (Jurnal Ekonomi & Kebijakan Publik, 2010)
In general, market participants using financial market indicator in measuring investment risk in the financial markets of a country. One factor that may investors be considered in investing at another country is the country’s economic fundamentals of debt issuer. In this case, the study will be conducted to determine the fundamental macroeconomic factors that influence to external debt risk. Buy using monthly data for period of 2005 until 2008, the result show that there are some significant factors that influence these indicators. The factors are current account per GDP and fiscal balance per GDP. Although based on empirical test result there are not all macroeconomic fundamentals significant, these factors should always be noted because basically these factors indicate the condition of Indonesia’s economic fundamentals.